2004
DOI: 10.1074/jbc.m401789200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of PEN-2 for Stabilization of the Presenilin N-/C-terminal Fragment Heterodimer within the γ-Secretase Complex

Abstract: ␥-Secretase is a protease complex composed of presenilin (PS), nicastrin (NCT), APH-1, and PEN-2, which catalyzes intramembrane cleavage of several type I transmembrane proteins including the Alzheimer's disease-associated ␤-amyloid precursor protein. We generated stable RNA interference-mediated PEN-2 knockdown cells to probe mutant PEN-2 variants for functional activity. Knockdown of PEN-2 was associated with impaired NCT maturation and deficient PS1 endoproteolysis, which was efficiently rescued by wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
129
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 48 publications
8
129
1
1
Order By: Relevance
“…To date, it is known that Pen-2 is a regulator of PS-1 endoproteolysis (23,25). Bergman et al (48) reported that the extreme C terminus of PS-1 is also essential for endoproteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it is known that Pen-2 is a regulator of PS-1 endoproteolysis (23,25). Bergman et al (48) reported that the extreme C terminus of PS-1 is also essential for endoproteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Pen-2 coordinately regulates proteolytic processing of PS-1 with Aph-1 (22) and is required for stabilization of the PS NTF/CTF heterodimer within the ␥-secretase complex (23). Aph-1 interacts with PS and Nicastrin and is required for intramembrane proteolysis of several ␥-secretase substrates (24,25).…”
mentioning
confidence: 99%
“…NCT is probably required as a sizeselecting substrate receptor (Shah et al 2005;Dries et al 2009), although recent findings may challenge such a function (Chavez-Gutierrez et al 2008;Martin et al 2009). PEN-2 apparently facilitates PS endoproteolysis into its active heterodimeric state and stabilizes PS within the g-secretase complex (Hasegawa et al 2004;Prokop et al 2004). No specific function has so far been assigned to APH-1, although it may act as a scaffold for the initial binding of NCT and assembly of the complex (LaVoie et al 2003).…”
Section: G-secretasementioning
confidence: 99%
“…This APH-1-NCT-PS1 complex then associates with PEN-2, resulting in the proteolytic conversion of ϳ42-50-kDa PS1 holoprotein into ϳ27-30-kDa NH 2 -terminal (NTF) and ϳ16 -20-kDa COOH-terminal (CTF) derivatives (5)(6)(7)(8)(9) that are the preponderant PS1-related polypeptides that accumulate in vivo (10 -12). Recent studies have revealed that PEN-2 also stabilizes the PS1 heterodimer (13,14). PEN-2, a 101-amino acid protein, contains two membrane spanning domains with the amino-and carboxyl-terminal domains facing the lumen (15,16).…”
mentioning
confidence: 99%